Analisis Kerusakan Sistem Electrical Pada Mesin Cnc Daito Drilling - Tyas Setyawati; Reni Rahmadewi (Peneliti.net, 2023)
In the Industrial Era 4.0 the machines used in development companies are especially very sophisticated and computer-based, especially at PT. Wijaya Karya Industri & Konstruksi Fabricasi Baja Majalengka almost all major machines use computer-based machines. The machine is the Daito CUD3C1050 Engine which is the first engine from Japan in Indonesia and even in Southeast Asia. Daito Drilling CNC Machine is classified as a new machine, so if there is damage to Daito Drilling CNC Machine, especially in the program, the problem solution is repaired by the engineer directly, the rest can be repaired by the equipment team. Machine availability affects the production process, if 98% is not achieved then the machine is not well prevented, the effect affects machine damage. If the availability of the machine is still below 98%, then the machine has an evaluation because it often occurs.